2015
DOI: 10.1021/acs.analchem.5b02630
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive FRET-FCS Detects Amyloid β-Peptide Oligomers in Solution at Physiological Concentrations

Abstract: Alzheimer disease (AD) affects around 30 million people, and the number is growing as life expectancy increases around the world. Pathologically, the disease is characterized by intracellular tangles formed by the microtubule-associated protein tau, and extracellular fibrillar deposits called amyloid plaques. The fibrils are composed of the amyloid β-peptide (Aβ), a proteolytic product generated from processing of the amyloid precursor protein (APP). A 40 residues long variant (Aβ40) is produced at high levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 40 publications
(92 reference statements)
7
42
1
Order By: Relevance
“…The distributions of R h for the Aβ40 and Aβ42 also overlap to a large extent (Figure 1(b)), and yield similar ensemble-averages (Table 1). For both the sequences, the R h values are in excellent agreement with (1.5-1.7 nm) NMR (53) and FCS experiments (54). The ratio R h /Rg for both Aβ40 and Aβ42 is ≈ 0.9, which implies that neither peptide behaves as a Gaussian chain, for which the ratios should be 0.640 and 0.665, respectively (55).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The distributions of R h for the Aβ40 and Aβ42 also overlap to a large extent (Figure 1(b)), and yield similar ensemble-averages (Table 1). For both the sequences, the R h values are in excellent agreement with (1.5-1.7 nm) NMR (53) and FCS experiments (54). The ratio R h /Rg for both Aβ40 and Aβ42 is ≈ 0.9, which implies that neither peptide behaves as a Gaussian chain, for which the ratios should be 0.640 and 0.665, respectively (55).…”
Section: Resultssupporting
confidence: 54%
“…The departure from standard homo-polymer theories is the first hint that sequence-specific effects as well as the inherent polyampholyte-like characteristic of the Aβ peptides, that are masked in moments of the distribution functions, need to be accounted for when describing their conformational ensembles. other measure of a polymer size, which is routinely estimated using dynamic light scattering (DLS), NMR, and FCS experiments (53,54). The distributions of R h for the Aβ40 and Aβ42 also overlap to a large extent (Figure 1(b)), and yield similar ensemble-averages (Table 1).…”
Section: Resultsmentioning
confidence: 90%
“…0.9-1.8 nm. [13][14][15][16][17] The average end to end distance follows a similar trend as the radius of gyration, with a value of 3.2 nm for Amber99SB*-ILDN and 2.7 and 2.8 nm for Charmm36mW without and with NaCl, respectively. The wide distributions of the end to end distance, shown in Figure S3, and the standard deviations of ∼1 nm indicate similar types of structural fluctuations in all three simulations.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 In terms of overall dimensions, the hydrodynamic radius of Aβ40 was measured to be ∼1.6 nm at room temperature 12 while for Aβ42 it adopts a range of values between 0.9-1.8 nm. [13][14][15][16][17] Computationally, the Aβ42 monomer structure has been studied with various simulating techniques and force fields. 18 The general picture that emerges from the numerous molecular dynamics (MD) simulation studies on Aβ monomer is that the observed structural characteristics are very diverse and highly dependent on the simulation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, investigation methods which can work at much lower concentrations, as optical techniques based on absorption and/or fluorescence detection, have been most widely employed to monitor in real-time the kinetics of the early aggregation processes in solution (20). In the last two decades techniques as fluorescence absorbance (22), photobleaching (19,23), self-fluorescent-quenching (20), fluorescence correlation spectroscopy (FCS) (24,25), fluorescence cross-correlation spectroscopy (FCCS) (26), dual-color fluorescence cross-correlation spectroscopy (dc-FCCS) (27), Förster resonance energy transfer combined with fluorescence correlation spectroscopy (FRET-FCS) (26), confocal two-color coincidence detection (cTCCD) (28), but also fluorescence imaging of labeled peptides (19,(29)(30)(31) or binding of Thioflavine T (ThT) (32) or Congo Red (33), have been widely applied for the study of such systems at very low concentrations. Despite the great sensitiveness of such optical techniques, one draw-back about using fluorescence is to be found in the inherent, yet necessary, modification of the original peptide system due to the attached fluorophore.…”
Section: Introductionmentioning
confidence: 99%